Using social practice theory in measuring perceived stigma among female sex workers in Mombasa, Kenya - Joseph Newton Guni; Stanley Wechuli Wanjala; Griffins Manguro; Caroline Gichuki; Megan SC Lim; Minh D. Pham; Stanley Luchters; James Orwa (BMC, 2023)
Abstract Background Perceived stigma is a complex societal phenomenon that is harboured especially by female sex workers because of the interplay of a myriad of factors. As such, a precise measure of the contribution of different social practices and characteristics is necessary for both understanding and intervening in matters related to perceived stigma. We developed a Perceived Stigma Index that measures the factors that greatly contribute to the stigma among sex workers in Kenya, and thereby inform a framework for future interventions. Methods Social Practice Theory was adopted in the development of the Perceived Stigma Index in which three social domains were extracted from data collected in the WHISPER or SHOUT study conducted among female sex workers (FSW), aged 16-35 years in Mombasa, Kenya. The three domains included: Social demographics, Relationship Control and Sexual and Gender-based Violence, and Society awareness of sexual and reproductive history. The factor assessment entailed Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA), and the internal consistency of the index was measured using Cronbach's alpha coefficient. Results We developed a perceived stigma index to measure perceived stigma among 882 FSWs with a median age of 26 years. A Cronbach's alpha coefficient of 0.86 (95% confidence interval (CI) 0.85-0.88) was obtained as a measure of the internal consistency of our index using the Social Practice Theory. In regression analysis, we identified three major factors that contribute to the perceived stigma and consists of : (i) income and family support (β = 1.69; 95% CI); (ii) society's awareness of the sex workers' sexual and reproductive history (β = 3.54; 95% CI); and (iii) different forms of relationship control e.g. physical abuse (β = 1.48; 95%CI that propagate the perceived stigma among the FSWs. Conclusion Social practice theory has solid properties that support and capture the multi-dimensional nature of perceived stigma. The findings support the fact that social practices contribute or provoke this fear of being discriminated against. Thus, in offering interventions to curb perceived stigma, focus should fall on the education of the society on the importance of acceptance and integration of the FSWs as part of the society and the eradication of sexual and gender based violence meted out on them. Trial registration The trial was registered in the Australian New Zealand Clinical Trials Registry, ACTRN12616000852459.